Analysis of Storage Spaces to Support the Health Service System at Santosa Hospital Bandung Central in 2021 - Tiny Rahayu; Encep Yayat; Agung Rachmat Raharja (Journal of Public Health Indonesian, 2024)
One of the health services provided by the hospital is the medical record service. The implementation of good medical file storage through systematic procedures is one of the keys to the success of health service, it is also one of this study was to determine the medical record storage space, the obstacles that occurred, and the effort made in the storage room at the Santosa Hospital Bandung Central. The research method used is descriptive qualitative research, by describing the relevant data. Data collection techniques in the form of interviews and document studies. From the results of the study it can be said that the layout and environment for storing medical records at Santosa Hospital Bandung Central is appropriate, the number of visits that continues to increase is not comparable to the medical record storage space contained in the storage room, the use of medical records is an effort made by Santosa Hospital Bandung Central. The use of electronic medical records overcomes problems in the storage space so as to minimize disruption of health services provided by the Santosa Hospital Bandung Central to patients.